Immune and metabolic perturbations in COVID‐19‐associated pulmonary mucormycosis: A transcriptome analysis of innate immune cells - Dhaliwal, Manpreet; Muthu, Valliappan; Sharma, Arunima; Raj, Khem; Rudramurthy, Shivaprakash M; Agarwal, Ritesh; Kaur, Harsimran; Rawat, Amit; Singh, Surjit; Chakrabarti, Arunaloke (Mycoses, 2024)
Background and Objectives The mechanisms underlying COVID‐19‐associated pulmonary mucormycosis (CAPM) remain unclear. We use a transcriptomic analysis of the innate immune cells to investigate the host immune and metabolic response pathways in patients with CAPM. Patients and Methods We enrolled subjects with CAPM (n = 5), pulmonary mucormycosis (PM) without COVID‐19 (n = 5), COVID‐19 (without mucormycosis, n = 5), healthy controls (n = 5) without comorbid illness and negative for SARS‐CoV‐2. Peripheral blood samples from cases were collected before initiating antifungal therapy, and neutrophils and monocytes were isolated. RNA sequencing was performed using Illumina HiSeqX from monocytes and neutrophils. Raw reads were aligned with HISAT‐2 pipeline and DESeq2 was used for differential gene expression. Gene ontology (GO) and metabolic pathway analysis were performed using Shiny GO application and R packages (ggplot2, Pathview). Results The derangement of core immune and metabolic responses in CAPM patients was noted. Pattern recognition receptors, dectin‐2, MCL, FcRγ receptors and CLEC‐2, were upregulated, but signalling pathways such as JAK–STAT, IL‐17 and CARD‐9 were downregulated; mTOR and MAP‐kinase signalling were elevated in monocytes from CAPM patients. The complement receptors, NETosis, and pro‐inflammatory responses, such as S100A8/A9, lipocalin and MMP9, were elevated. The major metabolic pathways of glucose metabolism—glycolysis/gluconeogenesis, pentose phosphate pathway, HIF signalling and iron metabolism‐ferroptosis were also upregulated in CAPM. Conclusions We identified significant alterations in the metabolic pathways possibly leading to cellular iron overload and a hyperglycaemic state. Immune responses revealed altered recognition, signalling, effector functions and a pro‐inflammatory state in monocytes and neutrophils from CAPM patients.